Crystallization and preliminary diffraction analysis of a DsbA homologue from Wolbachia pipientis - Kurz, M. (International Union of Crystallography, 2008)

(untitled)
α-DsbA1 is one of two DsbA homologues encoded by the Gram-negative α-proteobacterium Wolbachia pipientis, an endosymbiont that can behave as a reproductive parasite in insects and as a mutualist in medically important filarial nematodes. The α-DsbA1 protein is thought to be important for the folding and secretion of Wolbachia proteins involved in the induction of reproductive distortions. Crystals of native and SeMet α-DsbA1 were grown by vapour diffusion and belong to the monoclinic space group C2, with unit-cell parameters a = 71.4, b = 49.5, c = 69.3 Å, β = 107.0° and one molecule in the asymmetric unit (44% solvent content). X-ray data were recorded from native crystals to a resolution of 2.01 Å using a copper anode and data from SeMet α-DsbA1 crystals were recorded to 2.45 Å resolution using a chromium anode.